Application of the AISAS Model in Testing the Effectiveness of Smoking Prevention Knowledge Through TikTok Media on Adolescents - Anggraeni, Juwita; Rohmah, Nur; Nurrachmawati, Annisa (Pascasarjana, Mataram University, 2025)
Data from the Global Youth Tobacco Survey shows that although 78.9% of students received information about the dangers of smoking, high smoking prevalence remains among adolescents. This study aims to evaluate the effectiveness of the AISAS model in improving adolescent knowledge about smoking prevention through the social media platform TikTok. Using a one-group pre-test-post-test design in a quantitative approach, this study involved 54 seventh-grade students as sample using a proportionate stratified random sampling method. Data collection was conducted through questionnaires distributed before and after the intervention. Data analysis involved univariate and bivariate approaches, including the Paired Sample T-Test and Wilcoxon Signed Rank Test. The main finding was a significant increase in respondents' knowledge from pre-test (0%) to post-test (100%) after the intervention. Analysis using the Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of the intervention. Activities such as liking, commenting, and posting twibbons had a significant positive correlation with increased knowledge, with the activity of posting twibbons showing a B coefficient of 1.025 (p = 0.025). The results of this study indicate the importance of active involvement in social media as a key factor in increasing adolescent knowledge regarding smoking prevention